THE PROCESS OF LOCALIZATION OF GOVERNMENT OFFICES IN THE NATIONAL POLICY OF THE SOVIET POWER IN THE 20S OF THE XX CENTURY - Lutfillo Maxamadaliev (International Scientific and Current Research Conferences, 2021)
This article is devoted to the theoretical foundations of the localization of government agencies by the Soviet authorities in the 1920s and its implementation in the Turkestan ASSR.